A Missense Mutation in CD38 Associated with Autism Spectrum Disorder in Three Pedigrees - Higashida, Haruhiro; Munesue, Toshio; Yokoyama, Shigeru; Hashii, Minako; Koizumi, Keita; Matsushima, Akihiro (IntechOpen, 2011)
None